ENERGY SAVING THROUGH THE USAGE OF DOUBLE SKIN FAÇADE FOR GOVERNMENT BUILDINGS IN THE UNITED ARAB EMIRATES - FINIANOS, PATRICK JOSEPH (2018)
The United Arab Emirates is one of the leading countries in the development of cities. Dubai is one of the fastest growing cities in the world. One unique feature of Dubai is its structures and buildings. Most of the buildings in the city are characterized by being made using glass. The city is built on a desert, and this is a factor that has influenced the design and construction of structure because of the need for management of energy, ventilation, and lighting. The paper will provide a background of the subject as well as provide a study of the local region of study (Dubai), and some facts and statistics about the region. This paper contains the findings on the importance of the double skin façade in building consumption in Dubai. The study focuses on the importance of ensuring buildings in Dubai are fully glazed. The paper also focuses on the evaluation of DSF system for sustainable development in a hot climatic region such as that of Dubai. An overview of the literature of double skin façade demonstrating the different types of double skin façade is carried out along with several case studies of the different types of double skin façade carried out in different buildings from different locations. The literature review as well as the previous works of other researchers in the topic under discussion is also elaborated. The system under study as well as any other enveloping technologies is also explained with the aim of providing a better comprehension of the system and how it works. This will be discussed with reviews of other systems used around the world as well as the UAE region. The climate of the region which plays a crucial role in the study of this system is also discussed to provide a clear understanding of the climatic parameters. Also, the goals and objectives of this research are provided to identify the need for this research and what it seeks to explain or elaborate further. The paper also provides a discussion based on the findings of the research. Based on the advantages and benefits of this system, the paper will provide recommendations derived from the benefits of double skin façade. They include the allowance of natural ventilation, reduced artificial lighting, the improved comfort of buildings’ occupants, reduction of heating demand, control of solar gains, thermal insulation, and reduced energy consumption. This research will focus on various aspects of double skin façade regarding their design and implementation. It will explore the use of IES, experimental methods as well as a simulation to offer information on the effectiveness of double skin façade as a system for conservation of energy.